(untitled) (American International Journal of Agricultural Studies, 2020)
The influence of grasscover in restoring the eroded soils was carried out in Umudike, Southestern Nigeria. The use of grass has attracted considerable research attention with respect to forage production and erosion control. Little information is available on the influence of this grasscover management on soil physical and chemical properties. Four different grasses namely: Paspalum notatum(PN), Panicum maximum(PM), Axonopus compressus(AC) and Vetiver grass(VG)- Vetiveria zizanioid/es) were used in this study and their influence on eroded soil tested in two locations. This study has shown that the soils planted with the grasses gave significantly (p<0.05) higher results of the physical and some chemical properties than their adjacent open bare soil. In all the parameters considered in this study, the values obtained in soils under Paspalum notatum was higher than those obtained in PM, AC, VG and their adjacent bare soils(BS). The soils under PN had generally lower bulk density, higher total porosity and hydraulic conductivity than other grasses and adjacent open bare soil in both locations. The soil under PN proved best, outperforming PM, VG,and AC in stabilizing soil aggregates. Planting of PN on eroded soil significantly (p<0.05) increased the mean weight diameter from 0.77mm (BSPN1) to 1.31mm (PN1) and 0.82mm (BSPN2) to 1.48mm (PN2) for Locations 1 and 2, respectively. The relative improvement in Location 1 was in the order : PN1>AC1=VG1>PM1>BSVG1=BSPN1>BSAC1=BSPM1. Also, soils under PN had significantly higher values of pH, organic C and organic matter, total nitrogen and available P more than other grasses and their adjacent open soils. The magnitude of increase in Location 1 was in the order : PN1>AC1>PM1=VG1>BSVG1=BSPN1=BSAC1>BSPM1. Location 2 also increased in the same trend. The organic carbon content of PN increased from 0.73%(BSPN1) to 2.89%(PN1) and 0.88%(BSPN2) to 2.91%(PN2) in Locations 1 and 2, respectively. Also, the organic matter content of the soil increased in the same trend as organic carbon content.